2021
DOI: 10.22202/tus.2021.v7i1.4719
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Instruction for Efl Classroom

Abstract: Because each student is unique, the diversity in their learning and speed of learning needs to be considered to help them achieve the best process and outcome. As experts propose differentiated instruction as the method for reaching out to the students' uniqueness, the present article will elaborate the definition and characteristics of differentiated instruction, as well as its design, strengths, and weaknesses in English for Foreign Language context, in order to highlight the strength and weakness of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 23 publications
1
32
0
1
Order By: Relevance
“…Choosing instructional materials that are relevant to these nations may increase their motivation. A variety of activities such as requesting directions and engaging in other everyday discussions in Englishspeaking nations will help students develop a positive attitude toward the learning process (Suwastini et al, 2021).…”
Section: Differentiated Instructionmentioning
confidence: 99%
“…Choosing instructional materials that are relevant to these nations may increase their motivation. A variety of activities such as requesting directions and engaging in other everyday discussions in Englishspeaking nations will help students develop a positive attitude toward the learning process (Suwastini et al, 2021).…”
Section: Differentiated Instructionmentioning
confidence: 99%
“…Nevertheless, the present study revealed that students still needed guidance during the learning process to prevent them from being stuck and feeling lost. More straightforward and shorter instructions for the assignments can be understood by more competent students and their less-ready friends (Dwiyanti & Suwastini, 2021;Suwastini et al, 2021). Besides, the discussions in the comment sections can also act as scaffolding to provide additional explanations for students who need more guidance (Ersani et al, 2021).…”
Section: Appropriate Level Of Instructionmentioning
confidence: 99%
“…Despite the usability of Google Classroom for online learning, teachers should avoid using it to store the material and expect them to learn from the material pile. Teachers should not make one-size-fits-all material because students have different learning profiles, readiness, and interests (Ersani et al, 2021;Suwastini et al, 2021). The material stored in the platform should suit the learning theme and facilitate students' learning.…”
Section: Appropriate Level Of Instructionmentioning
confidence: 99%
“…If that happens, the teacher should be flexible with the topics to meet the students' different interests. The teacher should also adopt a certain degree of differentiated instruction to facilitate students with different proficiency levels and readiness, so the most competent students are kept challenged while the low-achieving students are not left behind (Ersani et al, 2021;Suwastini et al, 2021). Chaikovska (2018), Rakhmawati (2018), and Rokhayani & Utari (2014) recognize the challenge with the appropriateness of the comic strips' content with the students' age.…”
Section: Challenges In Using Comic Strips For Language Teachingmentioning
confidence: 99%
“…ccording to Gilakjani, Ismail, & Ahmadi (2011), each learner has their learning modality such as visual, aural, read or write, kinaesthetic, or even the combination of all this modality; hence it is called multimodal learning. A good teaching and learning process would consider the students' preferred modality (Ersani, Suwastini, Padmadewi, & Artini, 2021;Suwastini, Rinawati, Jayantini, & Dantes, 2021). One of the commonly used learning modalities is the visual modality.…”
Section: A Introductionmentioning
confidence: 99%